RISK ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY INTHE ROOF TILE INDUSTRY IN INDONESIA - Dakwatun Shofia; Ana Islamiyah Syamila (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: One of the Occupational Health and Safety (OHS) efforts to minimize risk is by carrying out risk management. The challenge in informal industries is that comprehensive risk analysis has not been carried out, so there is no control program to prevent work accidents. There have been work accidents in the roof tile industry due to various potential dangers that were not controlled beforehand. Purpose: To analyze the risks that exist in the roof tile manufacturing process. Method: This research uses descriptive research with a quantitative approach. This research was conducted in one of the roof tile industries in Indonesia. The units of analysis in this research are the process of mixing raw materials, grinding, molding, drying, and burning. The type of OHS risk analytical used is HIRARC, one of the implementations of ISO 31000 : 2018 for company risk management. HIRARC consists of hazard identification, risk assessment, risk evaluation, and risk control. Result: There are 89 potential hazards in the roof tile manufacturing process from. Most of the risks are low-level though there are still two categorized as very high. The results of the risk evaluation are categorized as Acceptable. Controls are carried out, starting from elimination until the use of Personal Protective Equipment (PPE). Conclusion: The most commonly identified hazards are physical hazards. Most risks fall to